Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17113941
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition in Childhood as A Risk Factor for Development of Social Anxiety Disorder: A Longitudinal Study

Abstract: Previous research has suggested the association between behavioral inhibition (BI) and the development of social anxiety disorder in childhood. However, there is scarce research using longitudinal methodology in Spanish-speaking populations. To cover this gap, the sample comprised 73 children ranging from six to eight years who had been examined for BI two years earlier in home and school settings. Children and their parents were administered the Anxiety Disorders Interview Schedule for DSM-5-Child and Parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…This temperament trait includes features of shyness, distress to novelty, and fear [12]. Early BI has been found to be a strong predictor for later SAD [13][14][15]. According to a retrospective evaluation by their parents, children with SM were rated as to be more behaviorally inhibited than children with SAD, children with internalizing disorders and typically developing children [16].…”
Section: Introductionmentioning
confidence: 99%
“…This temperament trait includes features of shyness, distress to novelty, and fear [12]. Early BI has been found to be a strong predictor for later SAD [13][14][15]. According to a retrospective evaluation by their parents, children with SM were rated as to be more behaviorally inhibited than children with SAD, children with internalizing disorders and typically developing children [16].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of social phobia are related to the temperamental trait behavioural inhibition (BI), which is characterized by reticence in new situations with unfamiliar people and objects 51 . Prospective studies of BI in early childhood found that this temperamental trait most strongly predicts subsequent social anxiety 52 , 53 , but also predicts other anxiety disorders 54 .…”
Section: Discussionmentioning
confidence: 95%
“…A well-examined and highly stable predictor of social anxiety in children and adolescent is behavioral inhibition (BI), which is a temperament style occurring in infancy and early childhood (Clauss and Blackford, 2012;Luis-Joaquin et al, 2020;Sandstrom et al, 2020). BI is based on a cognitive-behavioral mechanism that manifests itself as an exaggerated cognitive sensitivity to novel auditive and visual stimuli, and an avoidance of unfamiliar situations and people (Clauss and Blackford, 2012;Fox et al, 2005;Kleberg et al, 2021).…”
Section: Social Anxiety In School-aged Childrenmentioning
confidence: 99%